A copia-like retrotransposon insertion in the upstream region of the SHATTERPROOF1 gene, BnSHP1.A9, is associated with quantitative variation in pod shattering resistance in oilseed rape. (11th June 2020) - Liu, Jia; Zhou, Rijin; Wang, Wenxiang; Wang, Hui; Qiu, Yu; Raman, Rosy; Mei, Desheng; Raman, Harsh; Hu, Qiong
Abstract : Pod shatter resistance of rapeseed is influenced by a SHP1.A9 allele that contains a copia- like retrotransposon insertion in the promoter region, which silences SHP1.A9 expression epigenetically via DNA methylation. Abstract: Seed loss resulting from pod shattering is a major constraint in production of oilseed rape ( Brassica napus L.). However, the molecular mechanisms underlying pod shatter resistance are not well understood. Here, we show that the pod shatter resistance at quantitative trait locus qSRI.A9.1 is controlled by one of the B. napus SHATTERPROOF1 homologs, BnSHP1.A9, in a doubled haploid population generated from parents designated R1 and R2 as well as in a diverse panel of oilseed rape. The R1 maternal parental line of the doubled haploid population carried the allele for shattering at qSRI.A9.1, while the R2 parental line carried the allele for shattering resistance. Quantitative RT-PCR showed that BnSHP1.A9 was expressed specifically in flower buds, flowers, and developing siliques in R1, while it was not expressed in any tissue of R2. Transgenic plants constitutively expressing either of the BnSHP1.A9 alleles from the R1 and R2 parental lines showed that both alleles are responsible for pod shattering, via a mechanism that promotes lignification of the en b layer. These findings indicated that the allelic differences in the BnSHP1.A9 gene per se are not the causal factor for quantitative variation in shattering resistance at qSRI.A9.1 . Instead, a highly methylated copia -like long terminal repeat retrotransposon insertion (4803 bp) in the promotor region of the R2 allele of BnSHP1.A9 repressed the expression of BnSHP1.A9, and thus contributed to pod shatter resistance. Finally, we showed a copia -like retrotransposon-based marker, BnSHP1.A9 R2, can be used for marker-assisted breeding targeting the pod shatter resistance trait in oilseed rape.